Viral glycoprotein-mediated entry and antibody-mediated immunity in HIV-1 and SARS-CoV-2 infection - Grunst, Michael W.; Li, Wenwei; Mothes, Walther (Frontiers in Immunology, 2026)
Enveloped viruses such as Human Immunodeficiency Virus (HIV-1) and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have caused some of the deadliest pandemics in human history. These viruses utilize Class 1 viral fusion glycoproteins to bind their host receptor and subsequently fuse the virus and host cell membranes to mediate entry. Viral fusion glycoproteins are prominent antigens on the surface of virions and are essential for the virus life cycle. Therefore, they are a primary target for the humoral immune system and the basis for the design of vaccines. Antibodies which target viral fusion glycoproteins can neutralize viral infectivity and activate the immune system in several distinct ways. In this review, we compare mechanisms of how class 1 viral fusion glycoproteins mediate viral entry and cover diverse ways in which antibodies targeting these glycoproteins can neutralize viruses and activate the immune system to clear virus-infected cells.